Thermal Engineering Volume 2 - Kumar, Shiv.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This highly informative and carefully presented book offers a comprehensive overview of the fundamentals of thermal engineering. The book focuses both on the fundamentals and more complex topics such as the basics of thermodynamics, Zeroth Law of thermodynamics, first law of thermodynamics, application of first law of thermodynamics, second law of thermodynamics, entropy, availability and irreversibility, properties of pure substance, vapor power cycles, introduction to working of IC engines, air-standard cycles, gas turbines and jet propulsion, thermodynamic property relations and combustion. The author has included end-of-chapter problems and worked examples to augment learning and self-testing. This book is a useful reference to undergraduate students in the area of mechanical engineering.
Chapter 1: Properties of pure substance -- Chapter 2: Vapor power cycle -- Chapter 3: Introduction to working of IC engines -- Chapter 4: Air-Standard cycle -- Chapter 5: Gas turbines and jet propulsion -- Chapter 6: Thermodynamic property relations -- Chapter 7: Combustion.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Production engineering; Energy storage; Engineering Thermodynamics, Heat and Mass Transfer; Thermal Process Engineering; Mechanical and Thermal Energy Storage